PENGARUH CITRA MEREK DAN KUALITAS PRODUK SERTA HARGA TERHADAP KEPUTUSAN KONSUMEN MEMBELI AMPLANG BENGALON DI KOTA SANGATTA - ULFA, NUR MARIA (EKONOMIA, 2018)
Branch image is a set of assotiation (perception) appears on costumers mind toward the brand, ussualy organized to a meaning. Quality means the appropriateness with the specification, phisics, producer and qualification. Price is goods value stated with money. Generally, price is the amount of all values exchanged by consumer for owning of using the goos and service. Purchasing desigion is on evaluation level, consumers set the brands in selected group and form purchasing value. The hypotehesis of the research is brand image product quality and price influence positively and significantly toward costumer decision making to buy Amplang Bengalon in Sangatta. The research is quantitative research, in which the data source shawed in number. In this research researcher destributes 75 questionnaires to costumers of Amplang Bengalon by using Acciental sampling, a method to examine sampling coaecudentaly, to whom the researcher meet coaccidently can be data used in for sampling, if he is appropriate to be data source and for 3 mounths researcher decides 75 respondents.Model of analysis used in this research is multiple regression model. The linear of regression result is Y = 0,449 + 0,317X1 + 0,314X2 + 0,311X3 + e.The result of anaylisis test t shows that there’s positive and significant influence among brand image, product quality and price toward the cunsumer decision to buy Amplang Bengalon